Increasing The Community Capacity for Facing of Disaster Multi-Risk (Case Study in Dayu Village, Gondangrejo District, Karanganyar Regency) - Rita Noviani; Pipit Wijayanti; Chatarina Muryani; Ahmad Ahmad; Sarwono Sarwono; Sugiyanto Sugiyanto; Singgih Prihadi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Dayu Village which located in Gondangrejo Subdistrict, Karangnyar Regency has the potential disaster multi risks. Therefore, necessary to increase the capacity of Dayu Village community in facing disaster multi risks as anticipatory effort to minimize the impact of losses disasters in the future. The research used quantitative descriptive method with scoring and overlay analysis techniques, while for increasing community capacity through socialization related to the physical conditions of the area, FGD, participatory mapping, training and making evacuation routes. Based on the analysis results, it is known that Dayu Village has high level of disaster multi-risk. The results of FGD and participatory mapping showed that there were 6 points landslide and 1 point flood in Dusun Dayu  and 4 landslide points and 2 flood points in Dusun Tanjung. These location points used as reference in determining the location of the gathering point along with the evacuation route to that gathering point.